2021
DOI: 10.33024/jkm.v7i2.3411
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Perilaku Berisiko Pada Remaja

Abstract: FACTORS RELATING TO BEHAVIOR RISK IN TEENS Background: Physical and psychological development can lead adolescence to do risky behaviors, such as having premarital sex and using drugs. These behaviours are influenced by sociodemographic factor, knowledge, family function, and source of information on adolescent reproductive health.Objective: This study aimed to investigate risk factors associated with risky behaviors in adolescents (15-24 years old and unmarried) in West Java Province.Methods: Factors investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
6
0
2
Order By: Relevance
“…Adolescent boys have a stronger sexual drive and are more active in seeking sexual objects, besides that, it is related to norms that are even looser for men than for women in almost all parts of the world, and in connection with that, it is also more likely for men to do more things than women. These results are by research conducted by Padut et al (2021) where there were 32.4% more male teenagers who had risky sexual behavior than 9.2% of women. Rahayu et al (2020) stated that biological factors also influence men to have more risky sexual behavior.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Adolescent boys have a stronger sexual drive and are more active in seeking sexual objects, besides that, it is related to norms that are even looser for men than for women in almost all parts of the world, and in connection with that, it is also more likely for men to do more things than women. These results are by research conducted by Padut et al (2021) where there were 32.4% more male teenagers who had risky sexual behavior than 9.2% of women. Rahayu et al (2020) stated that biological factors also influence men to have more risky sexual behavior.…”
Section: Discussionmentioning
confidence: 62%
“…Among risky sexual behavior is sexual behavior committed by adolescents outside of legal marriage ties. As a result of sexual intercourse, about 12% were positive for sexually transmitted diseases, and about 27% were HIV positive (Padut et al, 2021). In Indonesia, there are around 4.5% of male youth and around 0.7% of female adolescents aged 15-19 admit to having had risky sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Karakteristik tersebut di antaranya meliputi usia, jenis kelamin, dan norma yang terdapat dalam keluarga. Wahdini, et. al, (2021) bahwa remaja laki-laki memiliki pergaulan yang lebih bebas dibandingkan dengan remaja perempuan karena kurang ketatnya pengawasan orang tua (Wahdini et al, 2021).…”
Section: Abstrakunclassified
“…Wahdini, et. al, (2021) bahwa remaja laki-laki memiliki pergaulan yang lebih bebas dibandingkan dengan remaja perempuan karena kurang ketatnya pengawasan orang tua (Wahdini et al, 2021). Namun sebaliknya, hasil analisis uji Chi-Square penelitian ini tidak sama dengan pendapat Riyadi (2015) yang menyatakan bahwa remaja laki-laki memiliki risiko penyalahgunaan NAPZA lebih tinggi daripada remaja perempuan (Riyadi, 2015).…”
Section: Abstrakunclassified
“…Teenagers have a fairly high curiosity, teenagers tend to be curious to try something that is driven by the desire to become an adult, including related to sexuality. The results of SKAP data analysis by Wahdini et al, showed the results of 4752 adolescents, 286 of them (6.2%) carried out risky behavior (Wahdini, Indraswari, Susanti, & Sujatmiko, 2021); research Parihat et al,of 967 adolescents,564 adolescents held hands (58.3%), kissed 217 adolescents (22.4%), held breasts of 81 adolescents (8.3%), held genitals of 56 adolescents (5.7%) and had intercourse with 27 adolescents ( 2.7%) (Parihat, 2015); Nadirahilah et al study showed that out of 135 adolescents, 74 adolescents (54.8%) had risky behavior and 29 adolescents (21.4%) had premarital sex (Nadirahilah & Nurdiansyah, 2019). Seeing this phenomenon the prevalence of adolescent risky behavior is increasing and the impact is also worrying.…”
Section: Premarital Sex Attitudes and Risky Behaviormentioning
confidence: 99%